The performance of rolled asphalt road surfaces proceedings of the conference held in London, 16 October, 1979. (Institution of Civil Engineers, 1980)
The topics covered within these papers are slippage of rolled asphalt wearing courses, permanent deformation of rolled asphalt, and skid resistance of rolled asphalt surfacings. A discussion of each paper is documented.
Keywords: Pavements, Asphalt -- Testing -- Congresses.; elektronické knihy; electronic books